The role of small and medium projects in sustainable development according to Vision 2030: An applied study on Al-Quway’iyah Governorate - Al-Qahtani, Munira Saeed (Journal of Economic, Administrative and Legal Sciences, 2020)
This research has aimed to highlight the role of small and medium projects in sustainable development according to the Kingdom’s Vision 2030 by identifying the role and outcome of these projects in sustainable development. 150 sample sizes were taken to study within Al Quwaiiyah KSA, Descriptive analytical method has been used and constructed questionnaire. The total agreeing of the study participants reached (80.8%) for the items "the role of small and medium projects in sustainable development", the most item was a contribution to product development and the emergence of new services on the market, providing society with new creative products; The total agreeing of the study participants reached (73.4%) for the item of axis " The role of the General Authority for Small and Medium institutions and the National Transformation Program in sustainable development " the most item was granting the authority incentives and offers for owners of small and medium institutions; The total agreeing of the study participants reached (73.4%) for the item of axis "the role of Vision 2030 in supporting small and medium institutions in development" " the most item was Vision 2030 provides many job opportunities for young people in small and medium institutions. Most significant study recommendations are workers, employees in the field of small and medium projects should increase their capacity building to avoid shortage of experiences and encouraging national experiences from various projects to support and train beginners in the field of small and medium projects.